Hybrid Mode Dispersion Characteristic Dependences of Cylindrical Dipolar Glass Waveguides on Temperatures - Asmontas, S.; Nickelson, L.; Bubnelis, A.; Martavicius, R.; Skudutis, J. (Elektronika ir Elektrotechnika, 2010)
In this work for the first time we present the dispersion characteristic analysis of open circular dipolar glass waveguides at the temperatures 130 ≤ T ≤ 200KWe demonstrate here the complex longitudinal propagation constants of the main mode HE11 in the frequency range from 1 GHz to 150 GHz for four values T when the waveguide radius is R = 1 mm. We give the propagation constant dependencies when waveguides have radii equal to 1 mm, 2 mm, 3 mm at T = 150 K. We present the dispersion characteristics of main HE11 and two higher hybrid EH11 and HE12 modes of the waveguide with the radius equal to 1 mm at T = 130 K. We demonstrate here also the waveguide broadbandwidth dependencies on the temperatures at three waveguide radii 1 mm, 2 mm and 3 mm. We discovered several important features of the dipolar glass waveguides that could be used for working out the microwave devices.